2009
DOI: 10.2169/internalmedicine.48.1339
|View full text |Cite
|
Sign up to set email alerts
|

Membranoproliferative Glomerulonephritis-Like Glomerular Disease and Concurrent Tubulointerstitial Nephritis Complicating IgG4-Related Autoimmune Pancreatitis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 31 publications
2
40
1
Order By: Relevance
“…Therefore, lymphoplasmacytic TIN with fibrosis and prominent IgG4-positive plasma cells seems to be a representative histopathologic feature of IgG4-RKD. Several kinds of glomerular lesions have been reported that overlap with those of typical lymphoplasmacytic TIN [11,23,24]. The most frequently reported lesion is membranous nephropathy (MN), and three patients had this type of glomerulopathy in this study.…”
Section: No (N)mentioning
confidence: 54%
See 1 more Smart Citation
“…Therefore, lymphoplasmacytic TIN with fibrosis and prominent IgG4-positive plasma cells seems to be a representative histopathologic feature of IgG4-RKD. Several kinds of glomerular lesions have been reported that overlap with those of typical lymphoplasmacytic TIN [11,23,24]. The most frequently reported lesion is membranous nephropathy (MN), and three patients had this type of glomerulopathy in this study.…”
Section: No (N)mentioning
confidence: 54%
“…IgG4-RKD is a new clinical entity in the field of nephrology, unrecognized before 2004, when the notion gradually emerged of it being an extrapancreatic manifestation of AIP [2][3][4][5][6][7][8][9][10][11][20][21][22][23][24][25]. This disease has many features helping to distinguish it from other types of TIN radiographically [26][27][28][29][30] and pathologically [11,21], and early detection provides the best chance for preservation of renal function because of its good responsiveness to corticosteroid therapy [2][3][4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Renal biopsy reveals diffuse lymphoplasmacytic infiltration of the renal interstitium, and the lesions vary from diffuse tubulointerstitial nephritis to tumor-like masses according to the distribution patterns of the infiltrating cells (21). On the other hand, glomerulonephritis associated with AIP is rare (22,23). Katano et al (23) …”
Section: Sions Sclerosing Cholangitis Sclerosing Sialadenitis Lympmentioning
confidence: 99%
“…Glomerular changes were evident in a quarter of the reported cases of IgG4-related tubulointerstitial nephritis (2). Among them, membranous nephropathy was dominant (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Membranous nephropathy, concomitant with IgG4-related tubulointerstitial nephritis, is considered linked to IgG4-related disease, but not a primary glomerular disease, because circulating anti-phospholipase A2 receptor antibodies, the most common autoantibodies in idiopathic membranous nephropathy (30), were undetected (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Hypocomplementemia and elevated antinuclear antibody (ANA) are frequently observed, whereas anti-SS-A, anti-SS-B, anti-Sm, anti-RNP and anti-double-stranded DNA (dsDNA) antibodies are generally negative (1). Occasionally, IgG 4-related tubulointerstitial nephritis accompanies glomerular diseases such as membranous nephropathy, mesangial proliferative glomerulonephritis and membranoproliferative glomerulonephritis; however, membranous nephropathy is dominant (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). We report a case, initially considered to be IgG4-related tubulointerstitial nephritis with membranous nephropathy requiring a differential diagnosis of membranous lupus nephritis (Class V) with severe tubulointerstitial changes.…”
Section: Introductionmentioning
confidence: 99%